The Impact Of Implementing Work Culture (Concise, Neat, Clean, Care, Diligent) And Nurse Competence On Nurse Productivity - Juliandri, Lukius; Melda, Byba; Anna Anggraeni, Novita (Journal of Applied Nursing and Health, 2024)
Background: Nurse productivity is crucial in determining the quality of healthcare services in hospitals. It directly impacts patient care and hospital operations. The implementation of Work Culture (Concise, Neat, Clean, Caring, Diligent) and nurses' competencies are factors that can significantly influence the productivity of nurses. The primary objective of this study is to determine the impact of Work Culture (Concise, Neat, Clean, Caring, Diligent) and nurses' competencies on nurses' productivity at Mojowarno Christian Hospital, Jombang, in 2024. The study assesses how applying these factors enhances nurse performance and hospital service efficiency. Methods: This research uses a quantitative approach with a cross-sectional design to examine the relationship between variables at a particular moment. The sample comprises 100 nurses from Mojowarno Christian Hospital, chosen through random sampling. The independent variables include the implementation of Work Culture (Concise, Neat, Clean, Care, Diligent) and nurse competencies, while the dependent variable is nurse productivity. Data collection was conducted using observation sheets tested for validity and reliability. Ordinal regression analysis was employed to analyze the data. Results: The results of the ordinal regression analysis showed a P-value of 0.000, which is less than 0.05, leading to the rejection of H0 and the acceptance of H1. This indicates a significant collective influence of the implementation of Work Culture (Concise, Neat, Clean, Caring, Diligent) and nurses' competencies on nurses' productivity. In the partial analysis, the P-value for the Work Culture (Concise, Neat, Clean, Care, Diligent) variable was 0.024, less than 0.05, suggesting a significant influence on nurses' productivity. The P-value for nurses' competencies was 0.000, indicating a significant partial effect on productivity. Conclusion: The study concludes that both the implementation of Work Culture (Concise, Neat, Clean, Caring, Diligent) and nurses' competencies have a significant impact on nurses' productivity at Mojowarno Christian Hospital. The results underline the importance of fostering a strong work culture and continuously improving nurses' competencies to enhance productivity and the overall quality of healthcare services. Hospitals should prioritize these factors to ensure efficient and effective care delivery, improving organizational outcomes. Keywords: Work Culture (Concise, Neat, Clean, Care, Diligent), competency, productivity.